MOTIVASI KERJA APARATUR PEMERINTAH DAERAH DI DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN SANGGAU - Lidia Carolina Christian E.42009018 (FISIP Universitas Tanjungpura Pontianak, 2022)
This script describes the motivation of employees in the Department of Energy and Mineral Resources of the District . The title was lifted by the problems that occur in the office of Energy regarding employee motivation is still relatively rendah.Penelitian using qualitative research methods with descriptive research . The data was collected using observation , interview and documentation . The research location is in the Department of Energy and Mineral Resources and the District is subject research apparatus in the Department of Energy and Mineral Resources of the District , as well as the manager of gas stations in Sanggau customers who deal in office EMR . As for the motivation of employees in the Department of Energy that needs career growth , job responsibilities will be , meaning civil servant status , working conditions , workload , the need for income , and family support.Based on the results obtained , are still visible lack of the spirit of the employees in the office at work as office facilities inadequate , it appears that employees feel uneasy because state offices were hot and cramped , relating to the officials also said in interviews that the lack of motivation to work because the state of the facilities and infrastructure that are not comfortable, do the work that still can not be done alone still ask the other employees , so sometimes interfere with the activities of other employees further still perceived weight challenges perceived by the employee of his job, Key Words: Motivation, Apparatus.